Immunization with WT1-derived peptides by tattooing inhibits the growth of TRAMP-C2 prostate tumor in mice - Babiarova, Katarina; Kutinova, Luda; Zurkova, Kamila; Krystofova, Jitka; Brabcova, Eva; Hainz, Petr; Musil, Jan; Nemeckova, Sarka (Journal of immunotherapy (Hagerstown, Md., 2012)
The expression of the transcription factor encoded by the Wilms tumor gene 1 (WT1) is associated with a variety of human cancers. WT1 protein has been reported to serve as a target antigen for tumor-specific immune responses. We observed that the immunization of mice with peptide vaccines derived from WT1 in a mixture with the CpG adjuvant (ODN 1826) by tattoo administration was superior to subcutaneous delivery of the peptides in combination with CpG formulated with the mineral oil adjuvant or a DNA vaccine or a recombinant vaccinia virus vaccine expressing the truncated WT1 protein. Tattooing with the WT1122-140 and WT1126-134 peptide elicited the response of WT1-specific interferon-γ-producing T cells. Peptide vaccine administered with a tattoo device had an antitumor effect on the growth of the prostate tumor cell line TRAMP-C2, provided that the transforming growth factor-β produced by tumor cells was neutralized by anti-TGFβ monoclonal antibody. The treatment of the tumor-bearing mice with 5-azadeoxycytidine or poly IC did not work in synergy with the peptide vaccine.
Keywords: injekce intradermální; Animals; Decitabine; azacytidin; Cell Line, Tumor; decitabin; Injections, Intradermal; Adjuvants, Immunologic; Transforming Growth Factor beta; Antibodies, Monoclonal; Cancer Vaccines; Tattooing; Antineoplastic Agents; Mice; protinádorové látky; transformující růstový faktor beta; Azacitidine; nádory prostaty; Mice, Inbred BALB C; WT1 Proteins; myši; Prostatic Neoplasms; protinádorové vakcíny; tetování; Male; myši inbrední BALB C; Vaccines, Subunit; proteiny WT1; poly I-C; subjednotkové vakcíny; monoklonální protilátky; zvířata; mužské pohlaví; adjuvancia imunologická; nádorové buněčné linie; Poly I-C